SARS-CoV-2 excretion kinetics in nasopharyngeal and stool samples from the pediatric population - Khemiri, Haifa; Gdoura, Mariem; Ben Halima, Samar; Krichen, Henda; Cammà, Cesare; Lorusso, Alessio; Ancora, Massimo; Di Pasquale, Adriano; Cherni, Asma; Touzi, Henda; Sadraoui, Amel; Meddeb, Zina; et al. (Frontiers in Medicine, 2023)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is responsible of serious respiratory infections in humans. Even in the absence of respiratory symptoms, gastrointestinal (GI) signs were commonly reported in adults and children. Thus, oral-fecal transmission was suspected as a possible route of infection. The objective of this work is to describe RNA shedding in nasopharyngeal and stool samples obtained from asymptomatic and symptomatic children and to investigate virus viability.Methods: This work included 179 stool and 191 nasopharyngeal samples obtained from 71 children, including symptomatic (n=64) and asymptomatic (n=7) ones. They were scheduled every 7 days from the onset of the infection, until negativation. Viral RNA was detected by real-time RT-PCR, targeting the N and ORF1 genes. Whole genome sequencing was performed for positive cases. Viral isolation was assessed on Vero cells followed by molecular detection confirmation.All cases included in this study (n=71) were positive in their nasopharyngeal samples. SARS-CoV-2 RNA was detected in 36 stool samples, obtained from 15/71 (21.1%) children, 13 were symptomatic and 2 asymptomatic. Excretion periods varied from 7 to 21 days and 7 to 14 days in nasopharyngeal and fecal samples, respectively. Four variants were detected: Alpha (n=3), B.1.160 (n=3), Delta (n=7) and Omicron (n=1). Inoculation of stool samples on cell culture showed no specific cytopathic effect. All cell culture supernatants were negative by RT-qPCR.Our study demonstrated nasopharyngeal and fecal shedding of SARS-CoV-2 RNA by children up to 21 and 14 days, respectively. Fecal shedding was recorded in symptomatic and asymptomatic children. Nevertheless, SARS-COV-2 was not isolated from positive stool samples.